1997
DOI: 10.1016/s0021-9150(97)00135-4
|View full text |Cite
|
Sign up to set email alerts
|

Costimulatory molecules in human atherosclerotic plaques: an indication of antigen specific T lymphocyte activation

Abstract: Atherosclerotic plaques contain inflammation, composed largely of macrophages and lymphocytes. A proportion of lymphocytes shows signs of activation, but the question arises whether they are activated in an antigen specific way. The expression of costimulatory molecules-receptors that provide accessory signals during antigen-specific activation is a prerequisite for such a condition. This aspect of inflammation in atherosclerotic lesions has not been investigated. Human arterial segments with diffuse intimal t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(57 citation statements)
references
References 32 publications
3
54
0
Order By: Relevance
“…Whereas production of helper cell-derived cytokines as IL-21 and IL-2 is limited to the antigenic activation phase, IL-15 can be produced by a number of lymphoid and nonlymphoid cells (44). It is feasible that viruses elicit distinct helper cell cytokine profiles by differential infection of APC and by different target cell tropism, thereby also determining the number and phenotype of CD8 ϩ T cells during the memory phase (45)(46)(47).…”
Section: Discussionmentioning
confidence: 99%
“…Whereas production of helper cell-derived cytokines as IL-21 and IL-2 is limited to the antigenic activation phase, IL-15 can be produced by a number of lymphoid and nonlymphoid cells (44). It is feasible that viruses elicit distinct helper cell cytokine profiles by differential infection of APC and by different target cell tropism, thereby also determining the number and phenotype of CD8 ϩ T cells during the memory phase (45)(46)(47).…”
Section: Discussionmentioning
confidence: 99%
“…Costimulatory and coinhibitory pathways have significant effects on atherosclerotic lesion development, as recently reviewed (133). The costimulators CD80, CD86, CD275, and CD252 can be detected on lesional macrophages in human and mouse lesions (134)(135)(136)(137)(138), as can their receptors on lesional T cells. A proatherogenic effect has been demonstrated for CD80, CD86, and CD252 (136,137,139) as well as for CD137, a costimulatory receptor expressed on T lymphocytes (138,140).…”
Section: Regulation Of Proatherogenic Adaptive Immune Responsesmentioning
confidence: 99%
“…Ϫ T cells in atherosclerotic plaques, an immunohistochemical study found that only a very low percentage (Ϸ10%) of T cells in human plaques express the CD28 antigen, 16 suggesting that many of the CD4 ϩ cells would result in CD28 Ϫ . In rheumatoid arthritis, levels of CD4 ϩ…”
Section: Cd28mentioning
confidence: 99%